PENGARUH APLIKASI GEL EKSTRAK CANGKANG KERANG HIJAU PADA EMAIL GIGI DESIDUI SETELAH PERENDAMAN MINUMAN BERKARBONASI - Susanto, William; Bramanti, Indra; Rus Sudarso, Iwa Sutardjo; Utomo, Rinaldi Budi (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Carbonated beverages are currently consumed by a significant number of children, despite the acidic properties of these drinks which can lead to tooth erosion. The deciduous tooth enamel is more susceptible to erosion due to its differences in structural and morphological composition compared to the permanent tooth. Green mussel shells have a high calcium carbonate content, which enables them to be used as synthetic hydroxyapatite to repair microporosity and remineralize deciduous tooth enamel. Aim: To investigate the effect of green mussel shell extract gel application on the microhardness and roughness of deciduous tooth enamel following immersion in carbonated beverages. Methods: A total of 25 anterior mandibular deciduous teeth were used in this study, which was divided into five groups. These were designated as the negative control group with gel base (K1), the positive control with CPP-ACP (K2), the green mussel shell extract gel group with 5% (P1), 10% (P2) and 20% (P3) concentrations. Each sample was treated for 21 days and immersed in carbonated beverages on days 1, 8, and 15. Thereafter, microhardness was measured using a Vickers Hardness Tester and roughness using a Roughness Tester. Data analysis was performed using one-way ANOVA. Result: The results demonstrated significant differences between the study groups in both microhardness and roughness testing. The highest result of microhardness was observed in group P3, with a mean of 222.72 ± 2.10. The lowest result in the roughness test was observed in group P3, with a mean of 0.35 ± 0.01. Conclusion: The green mussel shell extract gel at a concentration of 20% exhibited the highest microhardness and lowest roughness when compared to the 5% and 10% concentrations, as well as CPP-ACP on deciduous tooth enamel following immersion in a carbonated beverage.